César Vallejo: A chalice to immortality immortality - Manuel Chávez, Juan (2019)
The Abbey of Montserrat is a place in the mountains of the province of Barcelona, in Spain, with a history that goes back a millennium. Between tourists and pilgrims, an average of three million people arrive each year; the number represents three-quarters of the foreign tourists who visited Peru in 2017. This level of attention is explained not only by the geological vagaries of the landscape, with standing rocks that simulate agglomerated friars and the architectural monumentality of the Benedictine monastery with its vertical arches, but also because La Moreneta, the black Virgin who is the patron saint of Catalonia, is preserved there. A book by the poet César Vallejo is also kept there.